Socialization of Work Life Balance on Employee Performance and Job Satisfaction: A Human Resource Development Perspective - Agus Setiawan (Siber Nusantara of Community Service Review, 2025)
This community service activity carried the theme “The Influence of Work Life Balance on Employee Performance and Job Satisfaction”, organized by Universitas STEKOM on October 8, 2025, through the Zoom Meeting platform. The event was attended by 74 participants, consisting of students, practitioners, academics, and entrepreneurs, aiming to enhance understanding of the importance of balancing work and personal life to support employee productivity and well-being. The implementation method included interactive lectures, material presentations, and participatory discussions that encouraged participants to share experiences and practical solutions for applying work-life balance in their respective workplaces. The results showed that maintaining balance in life significantly influences both performance and job satisfaction. Employees who can effectively manage their time, energy, and personal responsibilities tend to exhibit higher levels of motivation, loyalty, and work efficiency. This activity also emphasized the essential role of organizations in supporting employees’ life balance through flexible work policies and healthy work environments. Thus, this community service initiative contributes meaningfully to strengthening the synergy between academia and the professional world toward developing human resources who are productive, fulfilled, and highly competitive.